Pilot Study to Evaluate the Efficacy and Safety of Oral Tacrolimus in Adult Patients With Refractory Severe Plaque Psoriasis. Issue 3 (May 2016) - Mittal, Ankit; Dogra, Sunil; Narang, Tarun; Sharma, Aman
Background: Tacrolimus, a congener of cyclosporine, has replaced cyclosporine as a first-line treatment for most transplant patients due to its superior efficacy and safety. Tacrolimus has not been extensively studied for the treatment of psoriasis. Objectives: To study the efficacy and safety of oral tacrolimus in adult patients with severe refractory plaque psoriasis. Methods: This was an open-label pilot study. Patients with severe plaque type psoriasis who were unresponsive to at least 1 systemic treatment were treated with oral tacrolimus. Results: Thirty patients were treated. After 12 weeks, improvement in mean Psoriasis Area Severity Index (PASI) score was 80.37% ( P < .001), PASI 75 was observed in 19 of 26 (73.1%) patients, and PASI 90 was observed in 11 of 26 (42.3%) patients. No severe side effects were noted. Conclusion: Oral tacrolimus is an effective and safe option for the short-term treatment of severe plaque psoriasis.